2001
DOI: 10.1021/np000582y
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Glycosides from Ruta graveolens

Abstract: An EtOH extract of the dried aerial parts of Ruta graveolens was suspended in water and then partitioned with EtOAc. Three new glycosides, 3'-sinapoyl-6-feruloylsucrose (4), methylcnidioside A (5), and methylpicraquassioside A (6), together with four known glycosides, 3',6-disinapoylsucrose (1), cnidioside A (2), rutin, and picraquassioside A (3), were isolated from the water-soluble part. Their structures were elucidated by interpretation of IR, MS, and 1D and 2D NMR spectra and comparison with literature dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…In the Siparuna guianensis ('negramina') were found flavonoids (Leitão et al, 2005), essential oils (Fischer et al, 2005) and alkaloids (Simas et al, 2001). Ruta graveolens ('arruda') contains alkaloids (Kuzovkina et al, 2004;Michael, 2005), flavonoids (Saieed et al, 2006), coumarins (Kostova et al, 1999), furanocoumarins (Ekiert and Czygan, 2005), triacylglycerines (Asilbekova, 2001) and glycosides (Chen et al, 2001). For Dorstenia asaroides ('caiá-piá') the phytochemical study showed the presence of furanocoumarins (Cardoso et al, 1999).…”
Section: Catalepsy Testmentioning
confidence: 99%
“…In the Siparuna guianensis ('negramina') were found flavonoids (Leitão et al, 2005), essential oils (Fischer et al, 2005) and alkaloids (Simas et al, 2001). Ruta graveolens ('arruda') contains alkaloids (Kuzovkina et al, 2004;Michael, 2005), flavonoids (Saieed et al, 2006), coumarins (Kostova et al, 1999), furanocoumarins (Ekiert and Czygan, 2005), triacylglycerines (Asilbekova, 2001) and glycosides (Chen et al, 2001). For Dorstenia asaroides ('caiá-piá') the phytochemical study showed the presence of furanocoumarins (Cardoso et al, 1999).…”
Section: Catalepsy Testmentioning
confidence: 99%
“…3 In Saudi Arabia, decoctions of the aerial parts of rue are a traditional treatment for fever, pain, rheumatism, and mental disorders. Fresh aerial parts of rue are a traditional treatment for palpitations and circulatory disorders in Taiwan.…”
Section: Medicinal Usesmentioning
confidence: 99%
“…The plant is often used for such varied conditions as hysteria, epilepsy, vertigo, colic, intestinal worms, poisonings, headache, anxiety and eye problems (Bejar et al, 1997;Estrada, 1996;Günaydin and Savci, 2005;Mansour et al, 1990;Perry, 1980). Phytochemical screening of Ruta species has characterized the presence of alkaloids, flavonoids, coumarins, tannins, volatile oil, glycosides, sterols and triterpenes as possible active constituents (Chen et al, 2001;Gray and Waterman, 1978;Grundon and Okely, 1979;Kostova et al, 1999;Mansour et al, 1990;Ulubelen et al, 1986). In fact, flavonoids, glycosides and tannins are considered potent inhibitors of pro-inflammatory signaling molecules (Iauk et al, 2004;Kanchanapoom et al, 2002;Viana et al, 1997Viana et al, , 2003.…”
mentioning
confidence: 99%